(untitled) - Morris-Suzuki, Tessa (London, 1989)
Economics--in the modern sense of the word--was introduced into Japan in the second half of the nineteenth century. However, by the seventeenth and eighteenth centuries, Japanese thinkers had already developed a variety of interesting approaches to issues such as the causes of inflation, the value of trade, and the role of the state in economic activity. Later, Western economic ideas were grafted onto these roots to provide the basis of debate between Marxist and neoclassical economists in early twentieth-century Japan. A History ofJapanese Economic Thought, now available in paperback, provides the first comprehensive English-language survey of the development of economic thought in Japan. Tessa Morris-Suzuki traces the principal currents in Japanese economic thought since the first half of the nineteenth century and shows how they have been influenced both by Japan's contact with the outside world and by the changing economic and social environment withinJapan. She examines the radical rethinking of fundamental economic theory now prevalent in Japan, and outlines some of the exciting new approaches which are emerging from this "shaking of the foundations.
Keywords: Economics,Kinh tế; History,Lịch Sử; Japan,Nhật Bản